Software quality assurance from theory to implementation - Galin, Daniel ([?], 2009)
Includes bibliographical references and index; 7 parts (26 chapters): Introduction; pre- project software quality components; QSA components in the project life cycle; software quality infrastructure components; management components of software quality; standards, certification and assessment; organizing for quality assurance.